Effects of Sildenafil and Vitamin E on Paraquat-Induced Pulmonary Fibrosis in Rats - Fouziyeh Siahpour; Hosein Sadeghi; Esmaeel Panahi kokhdan; Mohammad Khoshnoud (Trends in Pharmaceutical Sciences)
Paraquat, specifically concentrated in lung tissue, leads to lung damage through oxidative and inflammatory processes. Pulmonary fibrosis occurs due to inflammation and an imbalance in the antioxidant system. Drugs like sildenafil, which inhibits phosphodiesterase enzymes, are used to treat pulmonary arterial hypertension. Antioxidants such as vitamin E can restore the oxidant-antioxidant balance. This study aimed to evaluate the effects of sildenafil and vitamin E on paraquat-induced pulmonary fibrosis. Male Wistar rats were used in animal studies. Paraquat was administered orally (R1-1) at a single dose of 40 mg/kg to induce lung fibrosis. Three groups were studied: Sildenafil administered orally (10 mg/kg) for 14 days. Vitamin E administered orally (500 mg/kg) for 14 days. Simultaneous administration of vitamin E (500 mg/kg) and sildenafil (10 mg/kg) for 14 days. Biochemical and histopathological tests were performed and compared with a control group. Paraquat administration caused fibrosis and an oxidant-antioxidant imbalance in lung tissue. Treatment with sildenafil and vitamin E increased glutathione (total GSH) and superoxide dismutase (SOD) levels while decreasing malondialdehyde (MDA) and hydroxyproline (HYP) levels compared to the paraquat group. Tumor Necrosis Factor-α (TNF-α) showed no significant changes in the study group compared to the control group. Treatment with sildenafil and vitamin E improved the oxidant-antioxidant balance in lung tissue exposed to paraquat. Additionally, this study demonstrated significant antioxidant effects of sildenafil and vitamin E against paraquat-induced oxidative damage.